Perencanaan pengembangan Hortikultura pada Lahan gambut Menggunakan Analisis Sistem Informasi Geografi - Besri Nasrul (Jurnal Sagu, 2009)
Developing horticultural in the peat land needs geographical information system to gain data about its potential. The study was conducted at Meranti District, Riau Province at 2008. The result of study indicated that fruit crops (mango, durian, rambutan, soursop, avocado, mangos teen, citrus, jackfruit, banana, star fruit, papaya, and pineapple had the S2 land suitability for shallow-middle peat (50-200 cm). Based on this result, Meranti district has potential as a central of tropical fruits. The distribution of tropical peat land in Meranti district is about 263.647 ha or 64% tropical peat land.